U.S. Income Tax Transfer Pricing Rules For Intangibles as Approximations of Arm's Length Pricing. - Halperin, Robert; Srinidhi, Bin (The Accounting Review, 1996)
Multinational Enterprises (MNEs) have an incentive to shift income to lowertaxed jurisdictions. On July 1,1994, the Treasury Department issued intercompany transfer pricing regulations to mitigate such transfer of income resulting from the use of intangibles. The regulations give three alternative methods–(1) Comparable Uncontrolled Transactions (CUT), (2) Comparable Profit Method (CPM) and (3) Profit Split–to tax the intangibles. However, each of these three methods introduces incentives to the MNEs to alter resource allocations in comparison with a full-information optimum. In this paper, we examine the resource allocation changes under each method. The policy alternative to the use of such approximating measures is an increased attempt at direct valuation.